HLA-DQB1 6672G>C (rs113332494) is associated with clozapine-induced neutropenia and agranulocytosis in individuals of European ancestry - Konte, Bettina; Walters, James T. R.; Rujescu, Dan; Legge, Sophie E.; Pardiñas, Antonio F.; Cohen, Dan; Pirmohamed, Munir; Tiihonen, Jari; Hartmann, Annette M.; Bogers, Jan P.; Weide, Jan van der; Weide, Karen van der; et al. (Translational Psychiatry, 2021)
The atypical antipsychotic clozapine is the only effective medication for treatment-resistant schizophrenia. However, it can also induce serious adverse drug reactions, including agranulocytosis and neutropenia. The mechanism by which it does so is largely unknown, but there is evidence for contributing genetic factors. Several studies identified HLA-DQB1 variants and especially a polymorphism located in HLA-DQB1 (6672G>C, rs113332494) as associated with clozapine-induced agranulocytosis and neutropenia. We analysed the risk allele distribution of SNP rs113332494 in a sample of 1396 controls and 178 neutropenia cases of which 60 developed agranulocytosis. Absolute neutrophil counts of 500/mm3 and 1500/mm3 were used for defining agranulocytosis and neutropenia cases, respectively. We also performed association analyses and analysed local ancestry patterns in individuals of European ancestry, seeking replication and extension of earlier findings. HLA-DQB1 (6672G>C, rs113332494) was associated with neutropenia (OR = 6.20, P = 2.20E−06) and agranulocytosis (OR = 10.49, P = 1.83E−06) in individuals of European ancestry. The association signal strengthened after including local ancestry estimates (neutropenia: OR = 10.38, P = 6.05E−08; agranulocytosis: OR = 16.31, P = 1.39E−06), with effect sizes being considerably larger for agranulocytosis. Using local ancestry estimates for prediction, the sensitivity of rs113332494 increased from 11.28 to 55.64% for neutropenia and from 16.67 to 53.70% for agranulocytosis. Our study further strengthens the evidence implicating HLA-DQB1 in agranulocytosis and neutropenia, suggesting components of the immune system as contributing to this serious adverse drug reaction. Using local ancestry estimates might help in identifying risk variants and improve prediction of haematological adverse effects.